Regional governance in education: The case of the European Union and its implications for Latin America - Andrade Ortega, Esthela Alfonsina (2018)
The main purpose of this article is to analyze the consequences that the Bologna process has had for Latin American universities in the context of the regional governance in education. Indeed, the reform processes that have been implemented in Latin America the last decades have been strongly influenced by the European universities reform. This has caused a series of debates, agreements and division between the universities, the society, and State institutions, as those processes have been designed from outside the countries, thus making them unable to respond adequatelyto the requirements of society.